Photoluminescence and concentration quenching of Pr3+ doped BaTa2O6 phosphor - (:unkn) unknown (Faculty of Metallurgy, 2015)
The pure and Pr3+doped TTB-BaTa2O6phosphors were obtained by the solid state reaction method at 1 425 °C for 20 hours. X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM) analyses confirmed a single phase of BaTa2O6up to 10 mol % Pr2O3. SEM analysis also shows that BaTa2O6grain size decreased with the increasing Pr2O3concentration. The chemical composition of Pr3+doped BaTa2O6structures was confirmed by Energy Dispersive Spectroscopy (EDS) analysis. BaTa2O6:Pr3+phosphors exhibited on a strong red emission at 620,9 nm, a green emission at 548,3 nm and a red emission at 655,2 nm. Emission intensity increased with Pr3+doping concentration up to 1,5 mol %, then decreased due to concentration quenching. © 2014 Faculty of Metallurgy. All rights reserved.
Keywords: BaTa2O6; Phosphors; Pr3+; Solid state reaction; TTB